Young people facing the future : an international survey - Stellinger, Anna; Wintrebert, Raphaël; de Singly, François (Paris, 2008)
"What aspirations are motivating today's youth? How do they view family, employment, or society as a whole? As of what age is one considered “young”? At what age is one no longer young? In order to tackle these far-reaching issues, we are relying upon an international survey of 22,000 people conducted by Kairos Future Institute in partnership with the Fondation pour l'innovation politique: 1,000 young people aged 16 to 29, and 300 people aged 30 to 50, were interviewed in each of the 17 countries surveyed in Europe, Asia and in the United States. We have found that, far from being disengaged, today's youth is sending strong messages to politicians. Autonomy, participation, balance, and a collective project—such are the imperatives that must guide any youth-oriented political action."